Broadband ultrasonic focusing in water with an ultra-compact metasurface lens - Chen, Jian (2019)
Focusing of ultrasonic waves in water plays an important role in various scenarios ranging from biomedical imaging to nondestructive testing. Acoustic metasurfaces have been largely explored for acoustic focusing, but they are generally narrowband and mainly implemented for airborne sound because of their structural complexity. Nevertheless, our previous development of metasurfaces provides a great opportunity to solve the challenges. Here, we present numerically and experimentally the broadband focusing of ultrasonic waves in water with a metasurface lens consisting of an array of deep-subwavelength sized and spaced slots. The slot widths of the metasurface are optimized based on microscopic coupled-wave theory. Due to the non-resonant arrangement, the focusing effect is demonstrated over a broad band of frequencies. The metasurface lens with simplicity and an ultra-compact size provides a feasible means for the design of thin and lightweight ultrasonic devices and is suitable for practical applications in biomedical and industrial fields